2011
DOI: 10.1055/s-0031-1296703
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Butyrylcholinesterase Activity and Serum Lipids after Oxprenolol and Glibenclamide Treatments in Non-diabetic Rats

Abstract: SummaryThe effects of chronic treatment with oxprenolol (CAS 6452-72-7) (OXP, 15 mg/ kg/day), or glibenclamide (CAS 10238-21-8) (GL, 2.5 mg/kg/day), or their combination administered for 6 and 12 weeks, on the butyrylcholinesterase (BuChE) activity in plasma and liver and on the plasma levels of triglycerides, total cholesterol and high density lipoprotein (HDL)-cholesterol were studied in normal, non-diabetic female rats. In all treated groups a significant increase of plasma BuChE activity was obtained after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In addition to the contemporary widely accepted inflammation-induced insulin resistance, low-grade inflammation also accelerates amyloidogenic processes in brain and pancreatic b-cells. The results of Bradamante et al [16] also showed that increases in BuChE activity might be the first sign of altered triglyceride and lipoprotein metabolism in rats. Elevated level of BuChE occurs in diabetes and AD due to low-grade systemic inflammation, consequent to dysregulation of the described pathway.…”
Section: Discussionmentioning
confidence: 92%
“…In addition to the contemporary widely accepted inflammation-induced insulin resistance, low-grade inflammation also accelerates amyloidogenic processes in brain and pancreatic b-cells. The results of Bradamante et al [16] also showed that increases in BuChE activity might be the first sign of altered triglyceride and lipoprotein metabolism in rats. Elevated level of BuChE occurs in diabetes and AD due to low-grade systemic inflammation, consequent to dysregulation of the described pathway.…”
Section: Discussionmentioning
confidence: 92%